The Statistical point of view of Quality: the Lean Six Sigma methodology - Bertolaccini, Luca; Viti, Andrea; Terzi, Alberto (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Six Sigma and Lean are two quality improvement methodologies. The Lean Six Sigma methodology is applicable to repetitive procedures. Therefore, the use of this methodology in the health-care arena has focused mainly on areas of business operations, throughput, and case management and has focused on efficiency outcomes. After the revision of methodology, the paper presents a brief clinical example of the use of Lean Six Sigma as a quality improvement method in the reduction of the complications during and after lobectomies. Using Lean Six Sigma methodology, the multidisciplinary teams could identify multiple modifiable points across the surgical process. These process improvements could be applied to different surgical specialties and could result in a measurement, from statistical point of view, of the surgical quality.